1984
DOI: 10.1128/mcb.4.6.1125
|View full text |Cite
|
Sign up to set email alerts
|

Simian virus 40 large T-antigen point mutants that are defective in viral DNA replication but competent in oncogenic transformation.

Abstract: The large T antigen of simian virus 40 (SV40) is a multifunctional protein that is essential in both the virus lytic cycle and the oncogenic transformation of cells by SV40. To investigate the role of the numerous biochemical and physiological activities of T antigen in the lytic and transformation processes, we have studied DNA replication-deficient, transformation-competent large T-antigen mutants. Here we describe the genetic and biochemical analyses of two such mutants, C2/SV40 and C11/SV40. The mutants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 14 publications
4
46
1
Order By: Relevance
“…The mutations reported by Shuda et al (2) occur within the helicase part of the large T antigen of MCpyV and result in replication incompetence. This finding is reminiscent of early observations made by Gluzman and colleagues (8)(9)(10). That group reported that replication-defective SV40 virus DNA revealed an elevated transformation potential for various cell types.…”
Section: Transformation By Replication-deficient Virusessupporting
confidence: 74%
“…The mutations reported by Shuda et al (2) occur within the helicase part of the large T antigen of MCpyV and result in replication incompetence. This finding is reminiscent of early observations made by Gluzman and colleagues (8)(9)(10). That group reported that replication-defective SV40 virus DNA revealed an elevated transformation potential for various cell types.…”
Section: Transformation By Replication-deficient Virusessupporting
confidence: 74%
“…Subsequent molecular modeling studies indicate that a loop in T-ag centered on the highly basic ( 511 KKHLNKR 517 ) motif is situated opposite the boundary regions. That this motif might play an important role in DNA replication is supported by previous mutagenesis studies (53), for instance, those that characterized the Lys5163Arg mutation (42). While this conservative T-ag mutant bound to the core origin, it was defective in replication.…”
Section: Discussionsupporting
confidence: 58%
“…Similar results have been seen in vitro and in vivo for transformation studies of animal polyomaviruses. Gluzman and colleagues (25)(26)(27) reported enhanced transforming activity for defective SV40 with mutations disrupting viral replication and helicase activity. In vitro MuPyV-transformed cell lines lack LT protein expression required for viral replication but express MT and ST oncoproteins that do not encode the T antigen helicase domain (28).…”
Section: Discussionmentioning
confidence: 99%